2004
DOI: 10.1302/0301-620x.86b8.14732
|View full text |Cite
|
Sign up to set email alerts
|

Radiological changes in second- and third-generation Zweymüller stems

Abstract: The Alloclassic and Endoplus femoral stems have the same grit-blasted surface and are hot forged from the same titanium alloy. Only the external form of the implants differs slightly. It was our aim to examine the differences in radiographic bone response between the Alloclassic (second generation) and the Endoplus (third generation) femoral stems. We compared 79 prostheses in 70 matched patients studied over a minimum of two years. Radiolucent lines, adaptive bone remodelling, subsidence, heterotopic bone for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 37 publications
0
31
0
4
Order By: Relevance
“…Au to rzy zgod ni są rów nież co do fak tu za ob serwo wa nia li nii prze ja śnie nia czy za ni ku kost ne go wystę pu ją cych wo kół trzpie nia, naj czę ściej w stre fie 1, rza dziej w 7 [8,9]. Po mi mo po wy ższych ra dio lo gicznych ob ser wa cji, wy ni ki kli nicz ne pa cjen tów są satys fak cjo nu ją ce [10][11][12]. Nie licz ni au to rzy wska zu ją na wy stę po wa nie za gęsz czeń ko ści gąb cza stej pod trzpie niem, na to miast do tąd nie opi sa no me cha ni zmu sto ją ce go u pod staw te go pro ce su [1,[13][14][15].…”
Section: Wstępunclassified
See 2 more Smart Citations
“…Au to rzy zgod ni są rów nież co do fak tu za ob serwo wa nia li nii prze ja śnie nia czy za ni ku kost ne go wystę pu ją cych wo kół trzpie nia, naj czę ściej w stre fie 1, rza dziej w 7 [8,9]. Po mi mo po wy ższych ra dio lo gicznych ob ser wa cji, wy ni ki kli nicz ne pa cjen tów są satys fak cjo nu ją ce [10][11][12]. Nie licz ni au to rzy wska zu ją na wy stę po wa nie za gęsz czeń ko ści gąb cza stej pod trzpie niem, na to miast do tąd nie opi sa no me cha ni zmu sto ją ce go u pod staw te go pro ce su [1,[13][14][15].…”
Section: Wstępunclassified
“…Stan dar do wa pro jekcja AP jest naj czę ściej sto so wa na do oce ny po zy cji im plan tu i je go sta bil no ści. Tkan ka kost na pod le ga sta łej prze bu do wie i w wy ni ku dzia ła ją cych na nią sił do cho dzi do po ja wie nia się ob ja wów ra dio lo gicz nych ta kich jak: li nie prze ja śnie nia, re sorp cji bądź po grubie nia ko ści ko ro wej [12,16].…”
Section: Wstępunclassified
See 1 more Smart Citation
“…In comparison with the results of Zweymüller, Bicontact or Spotorno cohorts, the results for proximal calcar atrophy and radiolucent lines and distal hypertrophy are even slightly worse [3,24].…”
Section: Discussionmentioning
confidence: 99%
“…Long term studies of different cementless stems show a high incidence of stress-shielding, caused by the change in the distribution of loads on the femur (Engh et al, 2003;Glassman et al, 2006;Wick & Lester, 2004). The monitoring of an anatomic femoral stem with metaphyseal load-bearing and HA coating (ABG-I), that was carried out through a prospective, controlled study that included 67 patients (Group I) in the period 1994-99, has confirmed that even though the clinical results are very favourable, a high percentage of cases with stress-shielding are detected (Herrera et al, 2004).…”
Section: Application To the Behaviour Of Hip Prostheses Cementless Smentioning
confidence: 99%